The development of sympathy from 5 to 7 years: increase, decline or stability? A longitudinal study - Kienbaum, Jutta (Frontiers in Psychology, 2014)
In the present study the development of sympathy in a group of 85 children (43 girls) was investigated over a three-year period, starting with the last year of child care, when the children were five years old. Sympathy was measured via different measures: Two standardized observations, where the children were observed as they witnessed the distress of a puppet in two different situations; two follow-up interviews with the children immediately after the observations; a self-report questionnaire and two other-report questionnaires by parents and teachers. At all three periods the observations and the children’s self-reports (interviews, questionnaire) were intercorrelated. The teachers’ and the parents’ reports were not significantly correlated with any of the other measures at Time 1. At Times 2 and 3, a few low but significant correlations emerged. As a consequence, the other reports were dropped from further analyses and a composed sympathy measure consisting of observations and self-reports was created. Rank-order stability of this composed measure over the course of the three years proved to be high; suggesting that interindividual differences maintained stability. Mean-level differences showed a significant increase over the course of the study with the highest increase in the initial two years. Neither gender nor the interaction between gender and time were significant. In conclusion, the measurement of sympathy has proven valid for the childrens’ observations and self-reports. To the question of age-correlated development, stability in sympathy is firstly high and secondly sympathy increases mainly during the time between the last year in child care and the first year in elementary school.